2012
DOI: 10.1063/1.4709756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si-induced defects on 1 µm absorption losses in laser-grade YAG ceramics

Abstract: High sensitivity optical absorption at 1 lm was measured in 40 undoped and Nd-doped Y 3 Al 5 O 12 (YAG) transparent ceramics and single crystals using photothermal common-path interferometry. Concurrently, chemical trace analysis was performed on those samples by glow discharge mass-spectroscopy. Silicon and calcium were found to be the major impurities with concentrations up to 250 wt. ppm. A univocal linear correlation between the Si content and the absorption loss at 1 lm is revealed and a possible mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It thus appears that SiO 2 dopant does not inhibit the Cr ion from shifting valence state from 3+ to 4+ when added in combination with CaO, but it does prohibit the transformation of unstable octahedral Cr 4+ to tetrahedral Cr 4+ by generating local distortions in the YAG lattice. Gaume et al observed similar behavior with Si doping YAG and proposed that Si impurities can stabilize electrons near oxygen vacancies and form bound polarons. It seems likely that the same phenomenon is active in this study.…”
Section: Resultsmentioning
confidence: 74%
“…It thus appears that SiO 2 dopant does not inhibit the Cr ion from shifting valence state from 3+ to 4+ when added in combination with CaO, but it does prohibit the transformation of unstable octahedral Cr 4+ to tetrahedral Cr 4+ by generating local distortions in the YAG lattice. Gaume et al observed similar behavior with Si doping YAG and proposed that Si impurities can stabilize electrons near oxygen vacancies and form bound polarons. It seems likely that the same phenomenon is active in this study.…”
Section: Resultsmentioning
confidence: 74%
“…They determined Si doping YAG at levels below the solubility limit could not volatilized, meanwhile would result in the equilibrium segregation of Si to the grain boundaries. Additionally, the SiO 2 additives easily produce the optical absorption around 1 µm and lower the optical quality of Yb:YAG ceramics, even though for the low concentration of SiO 2 additives . Hence the microstructure evolution of Yb:YAG ceramics without the use of sintering additives were explored in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, SiO 2 is used as sintering aids to sinter YAG ceramics. When Si 4+ is substituted Al 3+ site, cation defect is generated and due to this lattice defect in the material, a small amount of optical absorption occurs around 1 μm wavelength regions, which causes the generation of heat during laser operation . In addition to SiO 2 sintering aids, other sintering aids such as CaO, MgO, and fluorites are also reported that they are useful to make fully transparent ceramics.…”
Section: Resultsmentioning
confidence: 99%